Slewing crane with electromagnet - Pedrosa, Delfim Duarte Rolo (2006)
This paper describes a slewing crane with electromagnet, operated by three three-phase induction motors. A switchboard described in a separate paper, which also depicts the electromagnet construction details, drives the motors and the electromagnet. From its seat – mounted on the crane - an operator can make the crane arm slew left or right. The electromagnet can be moved back, forward, up or down. The crane is made of iron, has a height of 3m and a length of 2,5m. Such proportions make it very suitable for science fair events.